Analysis Of Biochemical Oxygen Demand (BOD) Levels In River Water Samples: Analisis Kadar Biochemical Oxygen Demand (BOD) Pada Sampel Air Sungai - Safitri, Della (Program Studi S1 Teknik Kimia, Fakultas Teknik, Universitas Setia Budi, 2025)
This study aims to analyze Biochemical Oxygen Demand (BOD) levels in river water samples as an indicator of organic pollution. The method used refers to SNI 6989.72:2009, with the testing procedure including incubation of samples for five days at 20°C ± 1°C after the addition of nutrient solution and microbial suspension. Dissolved oxygen (DO) levels were measured before and after incubation to determine the oxygen requirements of microorganisms in decomposing organic matter. The results showed that BOD values in the samples ranged from 1.8 mg/L to 5.94 mg/L. These values are still below the quality standard threshold set in Government Regulation No. 22 of 2021, which is 30.5 mg/L. Variations in BOD values between locations indicate different levels of organic pollution, influenced by organic matter concentration, microbial activity, and environmental conditions. Locations with high anthropogenic activity showed higher BOD values than areas with better water flow or minimal waste. These results indicate that the water quality at the research location is still relatively good, but regular monitoring is still needed to ensure the sustainability of the quality of water resources. AbstrakPenelitian ini bertujuan untuk menganalisis kadar BiochemicalOxygenDemand (BOD) pada sampel air sungai sebagai indikator pencemaran bahan organik. Metode yang digunakan mengacu pada SNI 6989.72:2009, dengan prosedur pengujian meliputi inkubasi sampel selama lima hari pada suhu 20°C ± 1°C setelah ditambahkan larutan nutrisi dan suspensi mikroba. Pengukuran dilakukan terhadap kadar oksigen terlarut (DO) sebelum dan sesudah inkubasi untuk menentukan besarnya kebutuhan oksigen yang digunakan mikroorganisme dalam menguraikan bahan organik. Hasil penelitian menunjukkan bahwa nilai BOD pada sampel berkisar antara 1,8 mg/L hingga 5,94 mg/L. Nilai-nilai ini masih berada di bawah ambang batas baku mutu yang ditetapkan dalam Peraturan Pemerintah No. 22 Tahun 2021, yaitu 30,5 mg/L. Variasi nilai BOD antar lokasi menunjukkan tingkat pencemaran organik yang berbeda, dipengaruhi oleh konsentrasi bahan organik, aktivitas mikroorganisme, serta kondisi lingkungan sekitar. Lokasi dengan aktivitas antropogenik tinggi menunjukkan nilai BOD lebih besar dibandingkan daerah dengan aliran air lebih baik atau minim limbah. Hasil ini mengindikasikan bahwa kualitas air di lokasi penelitian masih tergolong baik, namun tetap diperlukan pemantauan berkala untuk memastikan keberlanjutan kualitas sumber daya air.